The influence of motivation on learning strategies used by ESL learners / Rowena Awali Ensanah - Rowena , Awali Ensanah (2014)
This study examines the learning strategies used by Pre-university students of different nationalities at Centre for Languages and Pre-University Academic Development (CELPAD) in Malaysia and the influence of motivation on these strategies. In this study the researcher examine how respondents of different gender, proficiency level, nationality and cultural background affect the choices of strategies used in an ESL/ EFL setting and if there is a significant relationship between motivation constructs of these English language learners and their nationality and gender. Oxford’s (1990) Strategy Inventory of Language Learning (SILL) questionnaire was employed to assess learners’ strategies together with a modified version of Attitude/ Motivation Battery Test (AMBT) questionnaire by Gardner to measure the motivation constructs of these English language learners. Pearson correlation together with descriptive statistics were also utilized to investigate any significant relationship between students’ language learning strategies and their motivations. The result showed that metacognitive strategy category was the most predominant strategy used, while memory and affective strategies were the least used. This study also observed that the overall frequency use of learning strategies were in the medium or average. Based on the SILL results, differences were positive but minimal in relation to proficiency level and gender, although there are no statistically significant relationships on strategies in relation to gender, proficiency level and nationality. This study also discovers that motivation does have a positive correlation on learners’ strategies. This study would be beneficial to educators, curriculum designers and learners as knowledge and understanding of one’s cultural background/ nationality may influence motivation and language learning strategy choice which are crucial in aspiring better learning performance and communicative competence.